Monetary policy and defaults in the US - Michele Piffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper uses a structural VAR model to study the effect of monetary policy on the delinquency rate of business loans and consumer credit. The VAR is identified using at the same time several external instruments, which cover different approaches from the literature. Delinquency rates, defined as the rate of loans whose repayment is overdue for more than a month relative to total loans, are found to decrease in response to a monetary expansion. The results are consistent with a general equilibrium effect formalized in the paper using a standard model of optimal defaults. According to the model, the decrease in defaults is driven by the fact that monetary expansions increase aggregate demand and push up profits and income, thereby improving the repayment possibility of borrowers.
Keywords: E52; E58; 330; monetary shocks; risk-taking channel; SVAR with external instruments